Assessment of Sea Water Inundation Along Daboo Creek Area in Indus Delta Region, Pakistan - Zia, Ibrahim; Zafar, Hina; Shahzad, Muhammad I.; Meraj, Mohsin; Kazmi, Jamil H. (Journal of Ocean University of China, 2017)
Indus Deltaic Region (IDR) in Pakistan is an erosion vulnerable coast due to the high deep water wave energy. Livelihood of millions of people depends on the fisheries and mangrove forests in IDR. IDR consists of many creeks where Daboo is a major creek located at southeast of the largest city of Pakistan, Karachi. Unfortunately, there has been no detailed study to analyze the damages of sea water intrusion at a large temporal and spatial scale. Therefore, this study is designed to estimate the effects of sea water inundation based on changing sea water surface salinity and sea surface temperature (SST). Sea surface salinity and SST data from two different surveys in Daboo creek during 1986 and 2010 are analyzed to estimate the damages and extent of sea water intrusion.Mean salinity has increased 33.33% whereas mean SST decreased 13.79% from 1987 to 2010. Spatio-temporal analysis of creek area using LANDSAT 5 Thematic mapper (TM) data for the years 1987 and 2010 shows significant amount of erosion at macro scale. Creek area has increased approximately 9.93% (260.86m2 per year) which is roughly equal to 60 extensive sized shrimp farms.Further Land Use Land Cover (LULC) analyses for years 2001 and 2014 using LANDSAT 7 Enhanced Thematic Mapper Plus (ETM+) has indicated 42.3% decrease in cultivated land. Wet mud flats have spread out at the inner mouth of creek with enormous increase of 123.3%. Significant sea water intrusion has increased the area of barren land by 37.9%. This also resulted in overall decrease of 6.7% in area covered by mangroves. Therefore, this study recorded a significant evidence of sea water intrusion in IDR that has caused serious damages to community living in the area, economical losses. Additionally, it has also changed the environment by reducing creek biological productivity as reported by earlier studies over other regions of the world.